Polycode text as a means of teaching technical vocabulary to engineering students - Prokopyuk, Olga V.; Solovyeva, Olga A.; Alipichev, Aleksei Yu; Sergeeva, Natalya A. (Вестник Томского государственного университета)
The article addresses the situation where engineering students learn foreign language vocabulary while facing a lack of professional expertise and having to retrieve most of professional information from the text in a foreign language. The aim of the article is to prove that the integral meaning of a term should be considered as a vocabulary teaching unit, and learners should fill its components by actively interacting with a polycode text in a foreign language. Based on linguistic studies, the authors determine the structure and the content of the educational model of the integral meaning of a term and outline its components (image perceptual, intentional, and implicational ones). They scrutinize the structure of a multicultural professional language personality to define the influence of a set of characteristics of the subject of professional activity on the ability to learn foreign language vocabulary. The article claims that motivational, linguocognitive, communicative, and other characteristics are formed in a special quasi-professional educational environment and condition the perception, understanding, processing and production of statements in a foreign language in a multicultural professional community. The article clarifies the potential utility of professional precedent texts for actualizing the integral meaning of a foreign-language term. Taking into account the linguodidactics provisions for designing figurative, verbal, and audiovisual blocks of a polycode text, this text format seems to be optimally suited for teaching and learning foreign vocabulary. The authors present empirical results of training, which were evaluated based on the criteria of completeness of conveying the content of the integral meaning of a term, and the accuracy of perception of terms presented in oral and graphic texts. The training was organized according to the following stages of foreign language vocabulary learning: (1) building of awareness of formal (graphic and sound forms) and meaningful (integral meaning) characteristics of the term; (2) understanding and actualization in speech of formal and meaningful characteristics of a term; (3) integration of the term with other units of the levels of the multicultural professional language personality. The vocabulary learning was based on the active exploration by engineering students of the language and professional information of interactive polycode texts. The results revealed the significant degree of interrelation between the aforementioned criteria and demonstrated that a higher level of students' mastery of the integral meaning of a term caused an increase in the lexical diversity of students' oral and written statements produced in English. The study confirmed the effectiveness of students' mastering the integral meaning of foreign language terms using the designed polycode texts.